strategy to develop the professionalism of the Islamic Education's teacher in SD Muhammadiyah 1 Blora year 2015 - ANWAR, SOLIHUL (2016)
ABSTRACT The purpose of this research is to describe the strategy to develop the professionalism of the Islamic Education's teacher in SD Muhammadiyah 1 Blora, its supporters and obstacles. It is an observation research that use the qualitative descriptive analysis and study case research. The method of data collection are interview, observation and documentation. The result of the result shows that, first, the strategy to develop the professionalism of Islamic Education's teacher in SD Muhammadiyah 1 Blora is done in the form of policy and the improvement of teacher's productivity, teaching skill through training, seminar and Teacher Working Group (KKG), the improvement of welfare, the improvement of the facility by providing religion books and the providing the additional classes. In the process of implementation of professionalism improvement policy of Islamic Education's teacher in SD Muhammadiyah 1 Blora, it is found that teacher's roles as educator, manager, administrator, supervisor, leader, innovator and motivator (EMASLIM) have not been maximized yet. The role as administrator, innovator and additional role as entrepreneurship have not been maximized, due to the lack of fund, facility and its supporters. Second, the professionalism of Islamic Education's teacher in SD Muhammadiyah 1 Blora meet the standard of professional, i.e. the qualification of education, competence and teacher certification. There are teachers in SD Muhammadiyah 1 Blora who administratively meet the professional standard, but they are lack of competence, such as professional and leadership competence. Third, the supporter of improvement Islamic Education's teacher professionalism in SD Muhammadiyah 1 Blora are 1) the availability of the teacher, 2) the support from school, the parents of the students and Muhammadiyah Association, 3) the support in the form of corporation between school, Muhammadiyah University in Blora and Local government of Blora regency. While the obstacles are internal and external factors. Internal factor is the teachers themselves, such as motivation and the need to improve their own quality. The external factors is the resources, fund, facility school policy, association and local government. Keyword : strategy; principal; profesionalism islamic education teacher